Analisis kebijakan kredit dalam upaya penagihan piutang travel agent di fairmont sanur beach bali - Ni Komang Riska Fildayanti; putu arnawan (Institut Pariwisata dan Bisnis Internasional, 2022)
This study aims to determine the credit policy applied at the Fairmont Sanur Beach Bali Hotel for the 2017 – 2019 period and to find out the factors causing delays in collecting travel agent receivables at the Fairmont Sanur Beach Bali Hotel for the 2017 – 2019 period. The data analysis technique used in this research is descriptive qualitative analysis technique. By using the analysis technique namely, account receivable turn over, average collection period, credit policy, credit standard, terms of credit and receivable collection policy.The results showed that there were deviations from the credit policy set by management, namely 12 times for the receivables turnover rate and 30 days for the average day for collection of receivables. But the realization is that in 2017 the receivables turnover rate was 7.25 times, in 2018 it was 6.71 times and in 2019 it was 6.11 times. Likewise, on the average day of collection of receivables, in 2017 it was 50 days, in 2018 it was 54 days and in 2019 it was 60 days. The hotel does not follow the standards set by the hotel management. The 5 C's of Credit have not been fully implemented in accordance with hotel policy. Likewise, not applying discounts and fines to travel agents. From the analysis that has been done, it can be concluded that the collection of receivables from travel agents at the Fairmont Sanur Beach Bali Hotel did not take place optimally.